Abnormal expression of histone acetylases in CD8+ T cells of patients with severe aplastic anemia. Issue 4 (10th March 2022) - Qi, Weiwei; Zhang, Yu; Wang, Yachen; Wang, Huaquan; Fu, Rong; Shao, Zonghong
Abstract: Introduction: We aimed to investigate the balance between the mRNA levels of histone acetyltransferases (HATs) and histone deacetylases (HDACs) in CD8+ T cells of patients with severe aplastic anemia (SAA). Methods: Twenty untreated SAA patients, 18 remission SAA patients (R‐SAA), and 22 normal controls were evaluated. The mRNA expression levels of HATs, HDACs, and IFNG in CD8+ T cells were measured by real‐time quantitative reverse transcription polymerase chain reaction. Results: Histone acetylase EP300 and CREBBP mRNA levels were significantly elevated in CD8+ T cells of SAA patients compared with the normal controls (both p  < 0.05). No significant differences were observed in HDAC1 and HDAC7  mRNA between SAA patients and the normal controls. There was an obvious positive correlation between IFNG and EP300 ( r  = 0.5126, p  < 0.01), and CREBBP ( r  = 0.4663, p  < 0.05), respectively, in SAA and R‐SAA patients. In addition, EP300 and CREBBP mRNA levels were clearly correlated with clinical parameters of peripheral blood and bone marrow in those patients. Conclusion: Our findings suggest that EP300 and CREBBP are increased in CD8+ T cells of SAA patients and are correlated with disease severity. The imbalances in HATs and HDACs may play a role in activating CD8+ T cells to promote the immune pathogenesis of SAA. Abstract : Increased expression of histone acetylation enzymes EP300 and CREBBP led to increased histone acetylation levels in CD8+ T cells of severe aplastic anemia (SAA) patients, which was correlated with abnormal activation of CD8+ T cells and the severity of SAA.